A Hybrid ACA-FDM for Electromagnetic Scattering from PEC Targets - Chen, Xinlei; Gu, Changqing; Deng, Xiaoqiao; Xu, Bingzheng; Li, Zhuo; Niu, Zhenyi (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, the adaptive cross approximation (ACA) algorithm is combined with the fast dipole method (FDM) to solve the electromagnetic scattering from perfect electric conducting (PEC) targets. In the ACA-FDM, the ACA and the FDM are employed to deal with the near-group pairs and the far-group pairs respectively. Compared with the conventional FDM, the submatrices related to the interactions of the near-group pairs are efficiently compressed by the ACA, so the ACA-FDM saves CPU time and memory requirement, when the criterion for the far-group pairs becomes stricter in order to obtain relatively high accurate solutions. Numerical results about the electromagnetic scattering from PEC targets are given to demonstrate the merits of the ACA-FDM.